Legal Review On Prospects For Filling In The Form Of Notary Protocol In Electronics Form And Legal Power - Restu Abiranda Bimaroni; Apromico Apromico; Munsharif Abdul Chalim (Jurnal Akta, 2019)
The purpose of this study is to 1. To know and analyze the prospects for a notary protocol archiving in electronic form, 2. To identify and analyze the force of law on notary protocol archiving in electronic form. The data used in this research is secondary data is data obtained through library research. Secondary data in this study is divided into two (2) in the form of primary legal materials and secondary law to support the study, then analyzed with descriptive analysis method.Based on the results of data analysis concluded that: 1) the prospect of a notary protocol archiving in electronic form can be judged from the aspect of economic and legal aspects. Economically, the electronic storage notary protocols aimed at more practical, efficient, cheap and safe. While the legal aspects, can assist and facilitate the legal proceedings related to the rules of evidence that electronic evidence. 2) The legal force of proof protocol notary electronically stored in evidence in the field of civil law can only serve as a backup and not as a copy of which has no binding force, due to the restrictions given by the ITE Law in Article 5 (4 ) that the electronic document that does not qualify the authenticity of the documents as stipulated in Article 1 point 1 UUJN Amendment and Article 1868 of the Civil Code, with the idea or discourse on the transfer protocol notary of conventional (paper based) into an electronic (digital based) then the notary profession in carrying out the authority and obligation to keep archives and documents in a notary's protocol will become more effective and efficient.Keywords: Normative Juridical Studies, Protocols Notary, Electronics.